New market opportunities for enterprising farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A productive agriculture offers many benefits: food for local consumption; raw materials for agro-industries; employment that generates income, which in turn encourages other industrial, commercial and service activities; export markets that can be...